The Effect of Discovery Learning Model by Integrating Virtual Writing Tutor on Students' Writing Achievement - Aprianti, Anggie Isma Aprianti; Linda Astuti Rangkuti; Meida Rabia Sihite (JL3T (Journal of Linguistics, Literature and Language Teaching), 2025)
ABSTRACT The objective of this research is to find out if Discovery Learning model by integrating Virtual Writing Tutor significantly affects students' writing achievement. The study's population consisted of tenth-grade students at SMA Negeri 11 Medan. There were 10 parallel classes at the tenth-grade, each consisted of 35 students. In the process of this study, two classes were selected as samples, resulting in a total sample of 70 students. Cluster random sampling technique was used in selecting the samples. This study employed a quantitative experimental design, and data were collected through written tests in the form of pre-tests and post-tests. The finding revealed that the use of Discovery Learning model integrated with Virtual Writing Tutor positively affected students' writing achievement. After the data analysis was conducted using t-test with SPSS version 20 software, the significance value (2-tailed) it was found that tobserved was higher than ttable (16.143 > 1.995) with the degree of freedom df =68 at the level of significance Î± =0.05. Therefore, it can be concluded that Hâ‚€ is rejected and Hâ‚ is accepted, indicating that the Discovery Learning model integrated with Virtual Writing Tutor significantly affected students' writing achievement. This approach can be considered an alternative strategy for delivering more interactive, engaging, and relevant writing instruction to meet students' learning needs in the digital era. Keywords: Discovery Learning Model; Students' Writing Achievement; Virtual Writing Tutor.